2019
DOI: 10.1128/jvi.00906-19
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation of Hepatitis C Virus NS2 Regulates Its Subcellular Localization and NS2-NS3 Autocleavage

Abstract: Chronic infection with hepatitis C virus (HCV) is a major cause of severe liver diseases responsible for nearly 400,000 deaths per year. HCV NS2 protein is a multifunctional regulator of HCV replication involved in both viral-genome replication and infectious-virus assembly. However, the underlying mechanism that enables the protein to participate in multiple steps of HCV replication remains unknown. In this study, we discovered that NS2 palmitoylation is the master regulator of its multiple functions, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…The cLD-associated mature Core recruits NS5A, presumably loaded with HCV RNA, to the same cLDs, which would trigger encapsidation [ 67 , 68 , 69 ]. Next, NS2 recruits envelope proteins E1 and E2 to the ER detergent-resistant membranes (ER-DRM) near the Core-decorated cLD [ 70 , 71 , 72 , 73 , 74 ], which likely trigger envelopment/budding of HCV particles into the ER lumen. NS2 palmitoylation facilitates NS2-mediated E2 recruitment to the virus assembly sites located at the ER-DRM, since inhibiting NS2 palmitoylation reduced ER-DRM localization of NS2 and E2, and colocalization of NS2 with cLD-associated Core [ 74 ].…”
Section: Role Of E2–p7 Cleavage Regulation In Hcv Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…The cLD-associated mature Core recruits NS5A, presumably loaded with HCV RNA, to the same cLDs, which would trigger encapsidation [ 67 , 68 , 69 ]. Next, NS2 recruits envelope proteins E1 and E2 to the ER detergent-resistant membranes (ER-DRM) near the Core-decorated cLD [ 70 , 71 , 72 , 73 , 74 ], which likely trigger envelopment/budding of HCV particles into the ER lumen. NS2 palmitoylation facilitates NS2-mediated E2 recruitment to the virus assembly sites located at the ER-DRM, since inhibiting NS2 palmitoylation reduced ER-DRM localization of NS2 and E2, and colocalization of NS2 with cLD-associated Core [ 74 ].…”
Section: Role Of E2–p7 Cleavage Regulation In Hcv Assemblymentioning
confidence: 99%
“…Next, NS2 recruits envelope proteins E1 and E2 to the ER detergent-resistant membranes (ER-DRM) near the Core-decorated cLD [ 70 , 71 , 72 , 73 , 74 ], which likely trigger envelopment/budding of HCV particles into the ER lumen. NS2 palmitoylation facilitates NS2-mediated E2 recruitment to the virus assembly sites located at the ER-DRM, since inhibiting NS2 palmitoylation reduced ER-DRM localization of NS2 and E2, and colocalization of NS2 with cLD-associated Core [ 74 ]. The coordination of HCV RNA replication and virus assembly was captured by the state-of-the-art imaging study by Lee et al, which showed cLD wrapping by the DMV-associated ER membranes and E2 recruitment to these membranes during HCV replication [ 75 ].…”
Section: Role Of E2–p7 Cleavage Regulation In Hcv Assemblymentioning
confidence: 99%
“…The requirement of at least one TM for proteolytic activity contrasts data on HCV NS2, where the cytoplasmic domain alone showed protease activity (50). However, the protease domain of HCV NS2 still requires membrane association via several other determinants for efficient protease activity (51,52). Nevertheless, for certain other members of the genus Hepacivirus, like bat hepacivirus (BHV), rodent hepacivirus (RHV), and GB virus B (GBV-B), it was shown that their NS2 protease requires its N-terminal membrane binding domain for catalytic activity (53).…”
Section: Resultsmentioning
confidence: 90%
“…FASN contributes to the replication of other viruses, like hepatitis C virus [129], HIV [130], dengue virus [131], and rotavirus [132]. And palmitoylation of viral proteins promotes binding to membranes, virus replication, entry into host cells and release of viral particles [133][134][135]. It is intriguing whether enhanced FASN palmitoylation could be a missing link in the molecular mechanism of virus infection and serve as a promising therapeutic target.…”
Section: Palmitoylation In Inflammation and Infection In Response To Fatty Acidsmentioning
confidence: 99%